Respostas

2014-06-25T14:34:25-03:00
1 )
a )

(f\circ~g)(x)=f(g(x))\\
\\(f\circ~g)(x)=f(3x)\\
\\(f\circ~g)(x)=9x^2+6x

b )

(g\circ~f)(x)=g(f(x))\\
\\(g\circ~f)(x)=g(x^2+2x)
\\(g\circ~f)(x)=3x^2+6x

2 )

a )

f(g(2))

g(2)=2.2+9\\g(2)=13

f(13)=2x+1\\f(g(2))=2.13+1\\f(g(2))=27

b)

g(f(-3))

f(-3)=2x+1\\f(-3)=2.(-3)+1\\f(-3)=-5

g(-5)=2x+9\\
\\g(f(-3))=2x+9
\\g(f(-3))=2.(-5)+9
\\g(f(-3))=-10+9
\\g(f(-3))=-1
1 5 1
Em a numero 1 e o finalzinho da dois apareceu assim[tex](f\circ~g)(x)=f(g(x))\\ \\(f\circ~g)(x)=f(3x)\\ \\(f\circ~g)(x)=9x^2+6x[/tex]
[tex](g\circ~f)(x)=g(f(x))\\ \\(g\circ~f)(x)=g(x^2+2x) \\(g\circ~f)(x)=3x^2+6x[/tex]
F5 , atualiza
ata, obrigada